2013
DOI: 10.4322/rbeb.2013.020
|View full text |Cite
|
Sign up to set email alerts
|

A influência do laser 830nm no desempenho do salto de atletas de voleibol feminino

Abstract: Resumo Introdução: Estudos demonstram que laserterapia pode melhorar o desempenho muscular e retardar o processo de fadiga muscular. Contudo poucos estudos referem-se à quantificação do desempenho por meio da biofotometria. O objetivo desse estudo é verificar os possíveis efeitos da fototerapia em relação a atividade e fadiga muscular. Métodos: Foi realizado um ensaio clínico duplo-cego controlado randomizado com sete indivíduos adultos, atletas universitárias de voleibol feminino, saudáveis. A atividade muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
3
Order By: Relevance
“…However, a later study, conducted with athletes by Maciel et al [49], which applied LLLT (830 nm) in the medial gastrocnemius muscle, showed no significant difference in the increase of the RMS signal (p = 0.1563), the force peak (p = 0.4219), and the onset of muscle fatigue (p = 0.2188). However, Muñoz et al [29] observed that the masseter muscle activity was significantly higher after LLLT (780 nm) (p < 0.05) compared to control values, even without significant differences in the values of strength and fatigue times (p > 0.05).…”
Section: Discussionmentioning
confidence: 86%
“…However, a later study, conducted with athletes by Maciel et al [49], which applied LLLT (830 nm) in the medial gastrocnemius muscle, showed no significant difference in the increase of the RMS signal (p = 0.1563), the force peak (p = 0.4219), and the onset of muscle fatigue (p = 0.2188). However, Muñoz et al [29] observed that the masseter muscle activity was significantly higher after LLLT (780 nm) (p < 0.05) compared to control values, even without significant differences in the values of strength and fatigue times (p > 0.05).…”
Section: Discussionmentioning
confidence: 86%
“…A fadiga muscular funciona como processo de defesa do organismo na tentativa de impedir que as reservas de energia do corpo se esgotem, pode ser caracterizada pela redução dos níveis de força, durante ou após um exercício físico (MACIEL et al, 2013 As mitocôndrias possuem fotorreceptores que captam energia irradiada pelo laser e um desses receptores é o citrocomo C oxidase (Cco), que é uma enzima responsável pela transferência de elétrons, processo que está diretamente envolvido com a produção de energia. Sendo assim, a TLBI pode aumentar a síntese de ATP pela aceleração das reações enzimáticas que ocorrem no processo de respiração celular, gerando uma adaptação metabólica nessa organela (SOUZA, 2013).…”
Section: Discussionunclassified
“…The benefits of LLLT in skeletal muscle include enhanced strength for everyday activities and sports, without damage to the fibers or reduced muscle functionality (Baroni et al, 2010;Caetano and Zanuto, 2013;Kelencz et al, 2010;Leal et al, 2009a;2009b;Liu et al, 2009;Lopes-Martins et al, 2006;Maciel et al, 2013). The dose and form of LLLT application were selected to primarily enhance cellular activity (Andrade et al, 2011;Lopes-Martins et al, 2007;Caetano and Zanuto et al, 2013;Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…with radiation different wavelengths (Andrade et al, 2011;Leal et al, 2010c;Lopes-Martins et al, 2007;Maciel et al, 2013;Place et al, 2010;Rocha and Barbanti, 2007).…”
Section: Discussionmentioning
confidence: 99%